The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/978-3-642-04268-3_64
|View full text |Cite
|
Sign up to set email alerts
|

Image Guidance for Spinal Facet Injections Using Tracked Ultrasound

Abstract: Abstract. Anesthetic nerve blocks are a common therapy performed in hospitals around the world to alleviate acute and chronic pain. Tracking systems have shown considerable promise in other forms of therapy, but little has been done to apply this technology in the field of anesthesia. We are developing a guidance system for combining tracked needles with non-invasive ultrasound (US) and patient-specific geometric models. In experiments with phantoms two augmented reality (AR) guidance systems were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 7 publications
(6 reference statements)
1
19
1
Order By: Relevance
“…In contrast to earlier findings [12], [16], these results suggest that EM-tracked facet joint injections may be routinely performed without ionizing radiation imaging.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In contrast to earlier findings [12], [16], these results suggest that EM-tracked facet joint injections may be routinely performed without ionizing radiation imaging.…”
Section: Discussioncontrasting
confidence: 73%
“…Similar tracked US guidance for facet joint injections was presented earlier [12]. A large, 4.87-mm average targeting error was reported with tracked US needle guidance.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Over the past two decades, several research groups have attempted to tackle this challenging problem [6][7][8]11,12,19,22,23]. To the best of our knowledge, these approaches have been validated either on single vertebra registration or on phantom and cadaver experiments.…”
Section: Introductionmentioning
confidence: 98%
“…Pre-operative computed tomography (CT) data were related to the acquired US volume via volume-to-volume registration and the electromagnetically (EM) tracked needle was guided towards the target using the information from the CT data during the intervention. Moore et al [19] proposed and evaluated three guidance approaches for facet joint injections based on intraoperative US and showed that the integration of a virtual CT-based model improved the accuracy of the injection. EM tracking was again used to relate CT and US information after a landmark-based registration was performed, and to provide the location of the needle accordingly.…”
Section: Introductionmentioning
confidence: 99%